Fully Implicit Ultrascale Physics Solvers and Application to Ion Source Modeling - Beckwith, Kris; Veitzer, Seth A.; McCormick, Stephen; Ruge, John; Olson, Luke N.; Cahoun, Jon C. (IEEE transactions on plasma science, 2015)
Many problems of interest in plasma modeling are subject to the tyranny of scales, specifically, problems that encompass physical processes that operate on timescales that are separated by many orders of magnitude. Investigating such problems, therefore, requires the use of implicit time-integration schemes, which advance problem solutions on the timescale of interest, while incorporating the physics of the fast timescales. One promising route to develop these implicit solvers is the combination of Jacobian-free Newton-Krylov (JFNK) methods, but adapting these methods to work in ultrascale computing environments is a formidable challenge. Here, we describe research on new approaches to adapt algebraic mulgrid-based solvers (that can be used for providing efficient preconditioners for JFNK methods) to ultrascale computing environments, the development and testing of JFNK solvers for coupled plasma electromagnetics within the USIM framework and the application of these methods to modeling H - ion sources for the spallation neutron source at ORNL.